2012
DOI: 10.1504/ijbpm.2012.047299
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency for Indian public sector and private sector banks in India: assessment of impact of global financial crisis

Abstract: Indian banking is undergoing major transformation since the financial sector reforms in 1990s. The objective of this paper is to investigate the extent to which global financial crisis has affected the efficiency of Indian banks. We measure production efficiency through application of data envelopment analysis. Data envelopment analysis is non-parametric technique of data envelopment analysis (DEA). In the research, interest income and non-interest income were used as outputs and interest expenses and non-inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The population of 42 PSBs and private sector banks in India has been sampled in the present study. Banks have been tools of rapid economic growth in India and their role is attributable to the indispensable role played by the PSBs and private sector banks in India (Bapat, 2012). The scheduled commercial banking structure in India consists of 21 PSBs (where majority of equity stake in the banks is held by the government), 21 private banks (where greater parts of equity stake are held by private shareholders) and 45 foreign banks (banks headquartered outside India, operate through wholly owned subsidiaries or branches).…”
Section: Methodsmentioning
confidence: 99%
“…The population of 42 PSBs and private sector banks in India has been sampled in the present study. Banks have been tools of rapid economic growth in India and their role is attributable to the indispensable role played by the PSBs and private sector banks in India (Bapat, 2012). The scheduled commercial banking structure in India consists of 21 PSBs (where majority of equity stake in the banks is held by the government), 21 private banks (where greater parts of equity stake are held by private shareholders) and 45 foreign banks (banks headquartered outside India, operate through wholly owned subsidiaries or branches).…”
Section: Methodsmentioning
confidence: 99%
“…While the performance of private‐sector banks was mixed, some banks performed better. Various studies have examined the impact of the global financial crisis and concluded that India, as an emerging country, was in a better position than other developed countries (Bapat, , ; Reddy, Nangia, & Agrawal, ). The present banking landscape is witnessing the entry of banks with different business models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By studying the distance relationship of the DMUs under the frontier with that of the efficient peer DMU, located on the frontier, one can quickly analyze the scope to enhance the output or limiting the inputs. In recent years, this method has gained the attention of many researchers and academicians, and thus there has been plenty of studies on the theoretical as well as practical applications of DEA (Bapat, 2012;Huguenin, 2013;Klimberg & Ratick, 2008;Silva et al, 2018;Yeh, 1996). Further (Sufian, 2007) stated that one of the major rewards of using the DEA technique for measuring efficiency differentials is that the technique is independent of the sample sizes and can be equally utilitarian for research, which comprises of less data for analysis.…”
Section: Data Envelopment Analysismentioning
confidence: 99%